Surgical treatment of solitary bone cysts in children using alloimplants - Baev, Vitaliy; Vorontsov, Petro; Gusak, Valerija; Samoilova, Kateryna; Slota, Oksana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
One of the traditional methods for treating solitary bone cysts (CCMs) is edge resection and defect replacement with bone or ceramic implants. Materials based on allogeneic bone after various types of processing that combine optimal properties for osteoregeneration may be promising. Objective: to evaluate the results of surgical treatment of children with CCMs using bone alloimplants for plastic surgery of post-resection defects. Methods: the results of examination and treatment of 11 patients (8 boys, 3 girls, age from 5 to 16 years) were analyzed. The diagnosis was established on the basis of the totality of the clinical manifestations of the disease, data from laboratory tests, X-ray and pathomorphological studies. The distribution according to the localization of the pathological focus: the proximal femur — 6 (54.5 %), the humerus — 2 (18.2 %), the heel — 2 (18.2 %), pubic — 1 (9.1 %). Indications for surgical treatment: the presence of a massive lesion of bone tissue in the loaded area, a high risk of pathological fracture, a pronounced longterm pain syndrome. All patients underwent regional resection and chemical processing of CCMs; defects were filled with osteoplastic material. Results: according to x-ray, bone remodeling in the surgical area occurred in 6–12 months. after operation. After 12–18 months the bone structure of the patients was corresponded to normal without or with plastic residues. Infectious complications, recurrences of the pathological process and repeated fractures were not observed, pain was absent, motor activity was restored. Conclusions: the studied osteoplastic material of allogeneic origin can be recommended for use in the surgical treatment scheme for CCMs in children for plastic surgery of post-resection defects to restore bone structure.